La lógica y el dilema de Benacerraf - Raúl Orayen (Crítica)
In this paper I point out three consequences that apparently follow from adopting one horn of Benacerraf's dilemma (the one rejecting abstract entities as objects referred to by mathematical language). These consequences are: